The settlement of Konoplyanka 2: a new site of the Cherkaskul’ Culture in the steppe Trans-Urals (results of research on line 1) - Panteleeva S.E. (Вестник археологии, антропологии и этнографии, 2024)
This article presents the results of chronostratigraphic analysis of cultural deposits in a sector of line 1 of the Konoplyanka 2 settlement in the southern Trans-Urals. During the excavations, materials of the Srubnaya (its Srubnaya-Alakul’ variant) and Cherkaskul’ Cultures were obtained. The Srubnaya-Alakul’ population was actively settling across this territory in the first third of the 2nd millennium BC. The Cherkaskul’ population came into the region later from the northern areas. Identification of Cherkaskul’ objects in the multilayer steppe sites is a topical scientific problem. During the excavations of the Konoplyanka 2 settlement, the remains of house 1, which contained four wells, a household pit and a sacrifice place were studied. Intriguing was the discrepancy between the obtained data and the results of the geophysical survey. While the intensive rounded magnetic anomalies, as expected, matched the wells and a household pit, the linear magnetic anomalies did not correspond to the contour of the house walls. Studies have revealed that house 1 was erected during the Srubnaya-Alakul’ building phase. Investigation of the spatial distribution of pottery was undertaken to clarify the position of the Cherkaskul’ deposits. The study included three analytical stages: the distribution of shards by depth, correlation of pottery types with soil layers, and the planigraphic distribution of fragments. As a result of this exercise, another structure — Cherkaskul’ house 2 — was found above the Srubnaya-Alakul’ house 1. Comparing the contours of this structure with the results of geomagnetic mapping suggests that the linear anomalies mark the walls of the actual Cherkaskul’ house. As such, two houses attributed to two building phases were identified at Konoplyanka 2; their dimensions and configuration were established, and the organization of the internal space has been considered. Noteworthy, the settlement does not contain layers of the final period of the Bronze Age. Due to this, we are dealing with a rare example of the satisfactory preservation of the Cherkaskul’ deposits. Thus, the settlement of Konoplyanka 2 contributes to the list of the known sites of the Cherkaskul’ Culture in the steppe Trans-Urals, representing a prospective object for further archaeological research.